Efficacy and safety of ozone therapy for knee osteoarthritis: an umbrella review of systematic reviews - Lino, Valéria T. S.; Marinho, Daniel S.; Rodrigues, Nadia C. P.; Andrade, Carlos A. F. (Frontiers in Physiology, 2024)
The objective of this study is to evaluate the effectiveness and safety of ozone therapy (OT) in the treatment of knee osteoarthritis (KOA), which is the most common form of the disease. We conducted an overview analysis of systematic reviews (SRs) of randomized controlled trials (RCTs) to assess the quality of the SRs using the "A Measurement Tool to Assess the Methodological Quality of Systematic Reviews" (AMSTAR2) instrument. We then performed a narrative synthesis report of the results, which included eight SRs (15 RCTs/3,685 patients). The AMSTAR2 analysis revealed that all reviews had critically low confidence results. Regarding the efficacy of OT in pain reduction, three SRs reported statistically significant results compared to placebo groups. However, in relation to other treatments, the efficacy of OT was similar in one SR and not superior in five SRs. Six SRs highlighted the need for additional RCTs with improved methodological quality to confirm the efficacy of OT for KOA. In terms of joint function improvement, the SRs identified less consistent effects. With regard to safety, seven SRs reported low incidence of mild adverse events associated with OT. In conclusion, this umbrella review highlights the beneficial effects and safety of OT in the treatment of KOA, particularly in pain control. The poor methodological quality of RCTs and SRs limits the possibility of drawing conclusions on the effectiveness of the technique compared to other treatments. Ensuring proper adherence to guidelines such as PRISMA and AMSTAR2 has the potential to enhance the quality of SR in this context.